Gestión de cobranza y su impacto en el presupuesto del gad municipal del cantón Buena Fe, período 2022 – 2023. - García Moreira , Joselyn Pamela (2023)
The management of collection and its impact on the budget of the Decentralized Government of the canton of Buena Fe, translates into a decrease in the Municipality's own income, affecting the management and provision of basic services and public works, as well as the ability to invest in projects of an economic nature may be affected For this reason, this research aims to evaluate the impact of collection management on the budget of the Municipal GAD of the Buena Fe canton in the period 2022 – 2023. The research methodology is qualitative-quantitative in nature thatwill allow us to address the problems of the topic to be investigated, for this it requires the application of inductive, deductive, historical-logical and descriptive methods, in order to evaluate and interpret the data obtained through direct observation, interview, survey and relevant documentation to evidence internal procedures as a collection tool, to establish the way in which collection procedures are carried out. As a result, the aim is to describe the shortcomings that have arisen, through a comparative analysis of the amounts issued versus those collected in order to evaluate the effectiveness of collection management and detect possible areas for improvement. The analysis of collection management in the Municipal GAD of Good Faith reveals challenges in the effectiveness and efficiency of collection, evidencing a decrease in revenue in the first half of 2023